Research progress on the drug resistance mechanisms of Candida tropicalis and future solutions - Xiong, Huisheng; Zhao, Rigetu; Han, Shizhe; Liu, Zhilin; Zhang, Xin; Jia, Zelin; Cui, Jiayu; Zhang, Yuhang; Wang, Xueli (Frontiers in Microbiology, 2025)
Candida tropicalis is an important member of the non-Candida albicans species. It is closely associated with candidemia, especially common in neutropenic and critically ill patients. Drug-resistant C. tropicalis isolates have been found not only in clinical patients but also in animals, fruits, and the environment. In recent years, the detection rate of azole-resistant C. tropicalis isolates has increased. Drug-resistant C. tropicalis is related to persistent, recurrent, and breakthrough infections. Therefore, understanding its drug resistance is crucial for clinical treatment. The review explores the main mechanisms of C. tropicalis resistance to antifungal drugs and discusses the genetic basis involved in the antifungal resistance of C. tropicalis. In addition, current research on natural extracts, nanomaterials, etc. used for antifungal purposes has also been reviewed. The aim of this review is that in-depth research on the drug resistance mechanisms of C. tropicalis resistant strains can help guide clinical medication. Meanwhile, it can also provide new ideas for opening up new pathways, searching for new targets, and screening out safe and effective “antifungal candidates,” with the expectation of improving the current clinical cure rates.